Tradisi Ijtihad dalam Islam (Dulu, Kini, dan Masa Mendatang) - Ahmad Minhaji (Jurnal Hukum IUS QUIA IUSTUM, 2001)
Today strong momentum exists in many quarters of Muslim world to reassert Islamic principles in social, economic, andpolitical spheres. This momentum often involves a quest for a new Islamic identity in the modem world, and may also include a redefinition oftraditional Islamic institutions. Countries as varied as Pakistan, Tunisia, Saudi Arabia, Indonesia, the Sudan, Bangladesh, and Iran are all grappling with the exigencies of industrial expansion and economic growth in the context of the international economy.